CLONING OF DENGUE VIRUS TYPE 3 (INDONESIAN STRAIN D3-1703) NON STRUCTURAL-1 GENE INTO pYES2/CT VECTOR (Makara Journal of Science, 2011)
Dengue is an infectious disease caused by dengue virus. Dengue endemic region includes America, Western Pacific, Africa, East Mediterranian, and South East Asia including Indonesia. An early diagnostic system specific for Indonesia is needed to control dengue in Indonesia. In this research, cloning of Non Structural 1 (NS1) gene from dengue virus type 3 (Indonesian strain D3-1703) into pYES2/CT vector was performed. In the long run, NS1 recombinant protein will be expressed in Saccharomyces cerevisiae for diagnostic materials. Polymerase Chain Reaction (PCR) amplification of NS1 gene fragments were done with optimal annealing temperature at 55 ºC. NS1 gene fragment and pYES2/CT were cut by BamH I and Not I enzymes. The digested pYES2/CT was dephosphosrylated using Calf Intestine Alkaline Phospatase enzyme. Ligation with the vector:insert ratio of 1:12 and 1:20 resulted in 6 and 5 recombinant colony candidates respectively. Restriction enzyme and PCR verifications showed that 5 recombinant plasmids contained NS1 gene. Sequencing of the first 600 bp of one recombinant plasmid was performed. The blastn analysis showed that it had a 99% identity with dengue virus type 3 strain FW06. Finally, it was shown that NS1 clone within pYES2/CT was in the correct Open Reading Frame and ready to be expressed in S. cerevisiae.